Pengaruh Kebijakan Utang, Profitabilitas dan Kepemilikan Manajerial terhadap Nilai Perusahaan - Djuharni, Darti; Kuncahyo, Adhin Achmad; Sonhaji, Sonhaji; Mauludin, Hanif (Asosiasi Ahli Administrasi Indonesia, 2024)
The purpose of this study is to determine the effect of debt policy, profitability, and managerial ownership on company value mediated by dividend policy. Data was obtained from the Indonesia Stock Exchange without financial sector companies during the period 2019-2021. The population for this type of company was 264, with a purposively determined sample of 35 companies obtained over three years of observation. The results of this study show that debt policy is not able to have a positive and significant influence on company value, but profitability is able to have a positive and significant influence on company value, In addition, managerial ownership is able to have a positive and significant influence on company value, The results of this study show that dividend policy cannot mediate positively and significantly the effect of policy Debt to company value, also cannot mediate positively and significantly the effect of profitability on company value, and cannot mediate positively and significantly the effect of managerial ownership on company value